The Implementation of Good Governance Principles in Permit Issuance Services (Study at the Intelligence Security Unit, Blitar City Police Resort) - Ameilia Nugraha, Rizki; Asih Wiludjeng, Ferida; Sutowo (Universitas Islam Balitar, 2024)
This research is motivated by the lack of public understanding regarding the procedures and requirements for the issuance of permits at the intelligence security unit of the Blitar City Police Resort. This study uses a descriptive method, employing Sedarmayanti's theory of good governance principles, which include accountability, transparency, participation, and the rule of law. The study's findings show that, on the whole, good governance concepts have been applied effectively when issuing licenses. The supporting factors for the implementation of good governance principles in the issuance of permits include human resources, public participation, equipment, as well as organization and management. However, there are some obstacles in the implementation of good governance principles in the issuance of permits, consisting of internal and external factors.